Augmented Reality as the Implementation of Digital Marketing 5.0 (Study Case: LPK Bali Aviation Tourism Center) - Ni Nyoman Pudak Sari; A.A. Istri Ita Paramitha; Tiawan; Ni Luh Putu Ning Septyarini Putri Astawa (ProBisnis : Jurnal Manajemen, 2023)
Gaining the attention of customers to raise our product's brand awareness is not an easy task, good planning and strategy will be needed to achieve it. This proves to be a big challenge for many companies, especially for Bali Aviation Tourism Center. Based on the latest social media trends the researcher suggested Bali Aviation Tourism Center to use Marketing 5.0 method. Marketing 5.0 strategy provides a new perspective on applying the technology from the social media Instagram, besides the advantages of creating content planning in using data driven marketing and predictive marketing, adding gamification impression using Instagram filter based on augmented reality in augmented marketing, being more personal with contextual marketing, and as far as keeping up with the rapid changes with agile marketing. Bali Aviation Tourism Center is a vocational education equivalent to Diploma 1 that is operating in the hospitality industry which provides students with trainings before working at the airport. This research will use descriptive quantitative method with marketing 5.0 for the analysis technique. The researcher applies marketing 5.0, using platforms such as Semrush, Google Trends, Spark AR, Canva, Watsap.id, and Trello. Research will then be done to find out the increase brand awareness of the company through Meta insight.